Identifying types of behavior of food SMEs towards food waste management - Isnaini Nurisusilawati; Halim Qista Karima (Center for Science and Technology, IAIN Surakarta, 2023)
Food waste is a significant sustainable challenge in Indonesia, particularly in commercial centers like Banyumas, it ranks as the second largest source of food waste. Despite the availability of information on food waste management, a substantial amount of food waste continues to be generated by food Small and Medium-sized Enterprises (SMEs). This research aims to categorize food SMEs in Banyumas based their food waste management behavior. The Extended Norm Activation Model framework was employed to assess the behavior of food SMEs in managing food waste. A questionnaire survey was conducted on 115 food SMEs in Banyumas, leading to the formation of two clusters through K-Means clustering: unmanageable and manageable. The unmanageable cluster exhibited the lowest levels of knowledge, awareness, and intention regarding food waste management and still requires substantial improvement in managing food waste. In contrast, the manageable cluster comprises food SMEs that have successfully implemented food waste management practices. These businesses demonstrate a heightened awareness of the food waste issue, take individual responsibility for addressing it, actively work to reduce waste. The finding of this research can serve as a basis fpr developing tailored mitigation strategies based on the behavior of SMEs in each cluster.